Evaluating the Performance of the Faculty at the University of Babylon in Light of the Requirements for Quality Higher Education (Journal of the College of Basic Education, 2025)
Concern for the quality of higher education has become a major concern in the field of educational work. The field of education is no different from other fields. Therefore, quality has become a criterion for the educational product and for achieving quality. This quality is the fundamental characteristic of educational institutions, which have faced a major challenge, emphasizing the need to improve the quality of education in light of technological, economic, and cognitive challenges, and to provide it with the highest possible quality. Focusing on the concepts of educational quality, which include improving faculty performance and developing programs, methods, and techniques used, helps achieve desired goals. This is primarily due to the teacher, who is considered the cornerstone of the academic institution. The researcher relied on the responses of (200) male and female students from the overall study community, using a tool consisting of (30) items after verifying its validity and reliability.In order to advance academic institutions in achieving positive change and renewal in various fields, their output must be distinguished by quality and quantity, and their inputs and outputs must be of a distinctive quality to achieve the desired university goals of teaching, scientific research, and community service and development. Therefore, periodic and continuous evaluation of the performance of employees in educational institutions is necessary, especially since education has recently received significant attention from the state, which has allocated the highest budgets for it. This reflects the importance of preparing effective human resources and their role in achieving development and progress.